Track of GPS-Drifter North_Sea_Drifter1 in the German Bight, Southern North Sea - Meyerjürgens, Jens; Badewien, Thomas Henry; Zielinski, Oliver; Braun, Axel; Butter, Michael (Institute for Chemistry and Biology of the Marine Environment, Carl von Ossietzky University Oldenburg, Germany, 2019)
Drifter position data from drifter deployments in March and October 2017 im the German Bight. The drifters were deployed from RV Heincke and RV Senckenberg. The drifter position was send every 10 minutes via the Globalstar satellite transmission service. The drifters were 0.5 m in height with a subsurface drogue which is directly to the housing. The drag area ration of the deployed configuration is R=25.6.
Keywords: Drifters; German Bight; North Sea